Hypnotic accumulation and hangover in elderly inpatients: a controlled double-blind study of temazepam and nitrazepam. Issue 6359 (8th January 1983) - Cook, P J; Huggett, A; Graham-Pole, R; Savage, I T; James, I M
Abstract : The hypnotic and residual sedative effects of the first and seventh of seven regular night-time doses of nitrazepam 5 mg, temazepam 20 mg, and placebo were studied in 58 elderly inpatients. Plasma temazepam and nitrazepam concentrations rose by about 50% and 113% respectively between the mornings of day 1 and day 7. Patients reported sleeping well more often after the first dose of either hypnotic (p less than 0.05), but there was no difference after the seventh dose. Reaction time was unchanged on the morning after the first dose but was significantly prolonged after the seventh dose of both hypnotics (p less than 0.01). The time taken to eliminate the letter E from a page of prose tended to be prolonged after the first dose of both drugs (temazepam v placebo, p less than 0.05; nitrazepam v placebo, not significant) and was further prolonged on the morning after the seventh dose of nitrazepam (nitrazepam v placebo, p less than 0.05). Thus plasma accumulation of the drug was associated with a deterioration in daytime performance. This change in performance did not correlate with age, cerebral blood flow, or plasma concentration, but patients of low intelligence tended to be more severely affected.